Importance of Hematite Self‐Reversal in Al‐Rich Soils Magnetostratigraphy: Revisiting the Damei Red Soil Sequence in the Bose Basin, Southern China. Issue 4 (31st March 2022) - Liu, Caicai; Qin, Huafeng; Ferré, Eric C.; Wang, Wei; He, Kuang; Deng, Chenglong
Abstract: Understanding the acquisition of chemical remagnetization that commonly takes place in sedimentary red beds is crucial not only to assess the stability of primary chemical remanent magnetization (CRM) but also to evaluate the impact of diagenesis on the paleomagnetic record. The inconsistency between the magnetostratigraphy and the 0.803 Ma age of tektites within the upper vermiculated unit of a red soil sequence (Damei) in southern China strongly suggests pervasive remagnetization. This remagnetization has previously been interpreted as a CRM lock‐in. However, our recent study suggests that the upper soil units of this section above the tektite‐bearing layer have experienced milder weathering than the underlying layer. It seems that CRM lock‐in has not completely overprinted the primary remanence of this section. To investigate the exact remagnetization mechanism, the magnetostratigraphy of the Damei sequence was revisited and the oriented samples were subjected to progressive thermal demagnetization up to 680°C (instead of 585°C in our previous study) by using a newly designed oven with ultralow magnetic field noise. The new demagnetization results for vermiculated and red clay samples document a high‐temperature (HT) remanence component above 630°C with some above 525°C, and a self‐reversal medium temperature (MT) component between 300 and 585°C. The magnetic polarities of most HT components are consistent with the tektite age. The self‐reversal MT component is carried by Al‐substituted hematite transformed from Al‐substituted maghemite. Self‐reversal likely occurred during the maghemite to hematite transformation process. Additional attention should be paid when using magnetostratigraphy to date highly weathered aluminum‐rich red sediments. Plain Language Summary: The information of the paleomagnetic field is crucial to understand the evolution of the geomagnetic field. Sediments are important carriers of paleomagnetic signals. Red beds, as a volumetrically significant type of sediment, are widely distributed in tropical and subtropical regions. The warm or hot climate in these areas favors the formation of red or brown iron oxides, such as hematite and maghemite, the former being always the main pigments of red beds. These iron oxides always carry a chemical remanent magnetization (CRM), which records the direction of the geomagnetic field when these minerals form. This type of CRM usually partially or completely overprints the detrital remanent magnetization (DRM) that was recorded when the red beds formed, and thus complicates paleomagnetic interpretations. In this study, by using a new thermal demagnetizer designed to have an ultralow magnetic noise, the weak DRM components of a strongly weathered red soil sequence have been successfully discriminated against despite being partially overprinted by CRM. This study revises the previous magnetostratigraphy which was only based on the CRM components. Our results suggest that additional attention should be paid when getting paleomagnetic information from highly weathered red sediments. Key Points: Weak high‐temperature remanence components discriminated by using a furnace with ultra‐low residual magnetic field Self‐reversed remanence carried by Al‐substituted hematite with unblocking temperature of around 640°C Self‐reversal of chemical magnetic remanence recorded on the transformation from Al‐substituted maghemite to Al‐substituted hematite